Evaluasi Program Pengelolaan Hipertensi di Puskesmas Keumala Kabupaten Pidie Provinsi Aceh - Nurul Rahmi; Afrilliansyah Afrilliansyah; Novrillia Novrillia; Dharina Baharuddin; Radhiah Zakaria (Pelantar Press, 2025)
Hypertension is a global health problem that contributes to high morbidity and mortality. A hypertension evaluation program in health services is needed to assess the effectiveness of interventions and to improve the quality of health services. The purpose of this study was to evaluate the hypertension management program at the Keumala Community Health Center, Pidie Regency, Aceh Province, in 2022–2024. The research method used a descriptive approach with a mixed method. Data collection techniques used the Keumala Community Health Center performance report for 2022–2024. The results of the study have shown progress in the implementation of community-based services. Increased human resources, budget, and logistics have provided a strong foundation for carrying out educational and preventive activities for hypertension patients. The implementation of routine exercise, regular drug distribution, and group education are the main pillars of this program’s success. The conclusion of this study is that this program has been effective in the short term, but long-term success depends heavily on the system’s ability to measure, monitor, and improve its implementation on an ongoing basis